DUALISME DE CROYANCE : ECHEC OU REUSSITE DU PREMIER MISSIONNAIRE EN AFRIQUE ET EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Baelongandi, Augustin Sombo; Botolome, Lambert Funga (IJRDO - Journal of Business Management, 2021)
In their dejected work, in African earth and in Democratic Republic of Congo, the first foreign missionaries played two roles: to announce Christ’s gospel and to sustain the colonial politics. The dismissal of the culture of the countries evangelized drove to the failure of these missionaries although the missionary work produced positive effects in the African and Congolese surroundings. We have included very quickly that as soon as a civilization succeeds in imposing itself to another, it is usually born a half-caste culture of which some values risk to fade away before those of the most influential civilization of the two. It is why, we wanted to contribute the custom that was in force in the way to believe the African evidently in writing, while granting priority to Christianity to correct, especially by African theologians themselves, the abuses of their own tradition.